Strategies to address coal mine-created environmental issues and their feasibility study on northeastern coalfields of Assam, India: a review - Choudhury, Aparna; Lahkar, Jiumoni; Saikia, Binoy Kumar; Singh, Anil Kumar Anil; Chikkaputtaiah, Channakeshavaiah; Boruah, Hari Prasanna Deka (Environment, development and sustainability, 2021)
Mining of coal around the world is being continued to meet the ever-growing energy demand. Mining involves extensive clearing of ground cover, change in physiography, generation of massive solid and liquid wastes to reach coal and thereby alters ecology and environment of the mining site as well as the neighboring areas. Depending on the nature, origin and seam arrangement of a coal reserve, mining method adopted on the site varies. These cumulative factors determine the impacts of coal mining on environment. To minimize the level of impact or to address various environmental issues caused by mining, evidence of many successful methodologies was described. However, all the processes are not universally applicable. Hence, the current review provided a comprehensive overview of coal mining environment, related damages and strategies employed globally for prevention, mitigation and remediation. Emphasis was given to analyze the feasibility of described methods to apply on northeastern coalfields (NEC) of Assam. Additionally, the review highlighted the reclamation measures used in NEC of Assam which generally produce a large amount of Tertiary coal concomitantly affecting the environment. Overall, the current review signifies proper utilization of suitable methods available globally to strategize effective measures relevant to northeastern coalfields of Assam.